2021
DOI: 10.3762/bjoc.17.67
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic reactions driven by electron-donor–acceptor (EDA) complexes

Abstract: The reversible, weak ground-state aggregate formed by dipole–dipole interactions between an electron donor and an electron acceptor is referred to as an electron-donor–acceptor (EDA) complex. Generally, upon light irradiation, the EDA complex turns into the excited state, causing an electron transfer to give radicals and to initiate subsequent reactions. Besides light as an external energy source, reactions involving the participation of EDA complexes are mild, obviating transition metal catalysts or photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 80 publications
(34 reference statements)
0
57
0
Order By: Relevance
“…[71] Initially, the photoredox properties of the Ni-complex were examined by carrying out various experiments like luminescence experiments, cyclic voltammetry experiments that suggested Ni(II)À TPP to exhibit dual redox properties i. e., it can undergo reductive as well as oxidative quenching. Using this as a photocatalyst, the annulation reaction was carried out using N,N-dimethylaniline (80), and maleimide (81) under oxygen atmosphere to provide tetrahydroquinoline derivative (82) (Scheme 31).…”
Section: Photoinduced Annulation Reactions For Cà H Bond Functionaliz...mentioning
confidence: 99%
See 3 more Smart Citations
“…[71] Initially, the photoredox properties of the Ni-complex were examined by carrying out various experiments like luminescence experiments, cyclic voltammetry experiments that suggested Ni(II)À TPP to exhibit dual redox properties i. e., it can undergo reductive as well as oxidative quenching. Using this as a photocatalyst, the annulation reaction was carried out using N,N-dimethylaniline (80), and maleimide (81) under oxygen atmosphere to provide tetrahydroquinoline derivative (82) (Scheme 31).…”
Section: Photoinduced Annulation Reactions For Cà H Bond Functionaliz...mentioning
confidence: 99%
“…This photoactive transient species involves the association of electron-rich (donor) and electron-deficient substrate (acceptor). [79,80] Although these substrates do not absorb the light individually, the EDA complex with these substrates absorbs light. The key feature of this milder synthetic methodology is that it does not rely on any exogeneous photocatalyst.…”
Section: Electron Donor-acceptor (Eda) Complex Enabled Photocatalytic...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, more economical and sustainable catalyst-free methods for chemical synthesis have emerged employing visible light irradiation to generate reactive intermediates in the absence of photocatalysts or photosensitisers. 8 Within this context, catalyst-free [2 + 1]-photocycloadditions of olefins with carbenes generated from diazo compounds have been developed. 9 For example, in 2018 Davies first demonstrated that electrophilic carbenes generated photochemically from diazoacetates underwent [2 + 1]-cycloaddition with unsaturated carbocycles and heterocycles ( Fig.…”
Section: Introductionmentioning
confidence: 99%